Analisis Daya Dukung (Carrying Capacity) dalam Mendukung Pengembangan Destinasi Pariwisata Pantai Batukaras Kabupaten Pangandaran - Riza Saepul MIllah; Siti Fadlina (STIEPAR YAPARI Bandung, 2023)
Tourism has become one of the industries that can have a large impact on the economy in Pangandaran Regency. One of the destinations, namely Batukaras Beach, has beautiful beach tourism attractions, especially for surfing sports lovers. The concept of Carrying Capacity of Batukaras Beach relates to the ability of a destination to absorb the impact of tourism development or development before the negative impact is real or occurs, and to pay more attention to its sustainability. This research methodologies uses quantitative and qualitative methods with primary data collection techniques through observation, surveys, and interviews. Secondary data collection uses various sources of literature, laws and regulations, statistical data, and others. This study aims to identify the four components of tourism destinations in Batukaras Village and calculate the carrying capacity of the tourism environment based on the biophysical aspects of the environment and management capacity in the Batukaras Beach tourism area using the formula developed by Cifuentes. The results of the calculation of the Effective Carrying Capacity (ECC) value of the Batukaras Coastal area are 1,048 per day, when compared to the current average number of actual visitors, visits on weekdays are 741 per day, still within the effective carrying capacity. Meanwhile, the number of visits on holidays, namely 2,464 visitors/day, already has a greater value and exceeds the value of the effective carrying capacity which has the potential to impact.